Geohazard features of the western Sardinia - G. De Falco; A. Conforti; G. Di Martino; S. Innangi; S. Simeone; R. Tonielli; F. Budillon (Journal of Maps)
The Maps of Geohazard features of the Western Sardinia produced by the Magic project (MArine Geohazard along Italian Coasts) were presented. The maps were created using morphobathymetric data obtained by surveying with a multi-beam echo sounder. The main potential geo-hazards on the western Sardinian margin are related with the presence of three pockmark fields which include hundreds of elements from few meters to several hundred meters in diameter. The pockmark fields are located ∼25–35 km off the coastline and at more than 400 m depth.